Bounds on third Hankel determinant for close-to-convex functions - Prajapat J. K.; Bansal Deepak; Singh Alok; Mishra Ambuj K. (Acta Universitatis Sapientiae: Mathematica, 2015)
In this paper, we have obtained upper bound on third Hankel determinant for the functions belonging to the class of close-to-convex functions.